Shear Reaction of Explosives and Propellants - Partom, Yehuda (European Journal of Applied Sciences, 2021)
When loaded by weak impact, both explosives and propellants undergo shear reaction. Out shear reaction hydro-reactive model (TDSR) is similar to our old surface burn hydro-reactive model (TDRR), except for the reaction rate equation. We perform tests and computer simulations of shear reaction in both explosives and propellants. For explosives we use the well-known Steven test but with different diagnostics (back surface velocity histories). For propellants we use a new test configuration. In both cases we run our TDSR simulations and are able to get a reasonable reproduction of test results.